Promosi dan Keputusan Penggunaan Layanan Jalur Nugraha Ekakurir (JNE) Bagi Pedagang Online di Masaran Kabupaten Sragen - Ipung Sri Purwanti Hery; Hariyanti Hariyanti (STIE AUB Surakarta, 2022)
The rise of delivery and online business industries in Indonesia has an impact on the intense competition for delivery goods at domestically/abroad. The study identified that the effectiveness of promotion made JNE superior to other delivery companies. The theories of Tjiptono (2008); and Nugroho (2005) stated that service use decisions that based on certain preferences including promotions. This study aims to determine whether promotion influences the decisions to use JNE for online traders in Masaran District. Sragen Regency. This study used a quantitative approach, by optimizing 100 respondents of online traders as samples and was taken by accidental sampling technique. Questionnaire was to be the instrument for collecting data. The data obtained were tested by Linear Regression Test, t Test and R2 Test. The linear regression and the t test result show that the promotion has a significant positive effect on the decision to use JNE services. R2 Test Results obtained number of 0.873 or 87.3 % the decision to use JNE is influenced by promotion, the remaining 12,7% is influenced by other variables. The results of this study can be used as guidelines, recommendations, references and material for the company and other future researches related to marketing.